THE COMPARISON OF PROBABILITY ISSUES OF A STATISTICAL LITERACY - Almeida, Catia Candida de [UNESP] (Inst Fed Education, Science & Technology Of Goias, Campus Inhumas, 2018)
This paper aims to compare the responses of Australian students and Brazilian students regarding issues involving probability contents addressed in a statistical literacy assessment instrument. Thus, we selected two probabilities questions from this instrument, being applied with Australian and Brazilian students. The same instrument was applied with Brazilian students, elementary education II, in four public schools. The comparisons of the students' responses were then performed. The comparisons of the answers showed that Brazilian students present difficulties similar to those of Australian students in understanding the contents that involve probability It should be noted that mathematics teachers have a fundamental role in promoting statistical literacy.
Keywords: educational evaluation; statistical literacy; probability; elementary school